Physicochemical Characteristics Identification and Secondary Metabolite Analysis of Solid Herbal Waste as Source of Feed Rich Fiber and Supplement for Ruminants - Kisworo, Arif Nindyo; Agus, Ali; Kustantinah, Kustantinah; Suwignyo, Bambang (ANIMAL PRODUCTION, 2016)
A study was conducted to determine the potency, physicochemical characteristics, and analyzed the secondary metabolites content of solid herbal waste (SWH) as a substitute source of feed rich fibre and feed supplements in ruminants. The first study includes an analysis of production potential, physical analysis, and chemical composition analysis of SWH. The second study was an analysis of secondary metabolites content of SWH. The results showed that SWH volume reached 6-8 m3/day or 4020-5360 kg/day, the chemical composition of herbal solid waste was similar to king grass with high lignin content (17.53%). SWH containing total phenols, flavonoids, tannins, saponins , alkaloids and essential oils which generally have antimicrobial activity. According to the potential availability, chemical composition and secondary metabolites content of SWH, it can be used as an alternative for substitute of feed rich fiber or feed supplements with attention to the content of secondary metabolites that can affect the process of fermentation and digestibility in the rumen. Further in vitro and in vivo research ore needed to determine the effect of SWH on rumen fermentation parameters and its application in the ration in ruminant livestock.